MODELLING OF VIBRATIONS OF PRODUCTS AND CABLES AT DYNAMIC TESTS - S.A. SHAMSHURA; A.N. CHUKARIN (Advanced Engineering Research)
In article the dynamic model of the stand of tests for cyclic durability of longerons of helicopters is considered. Dependences for the theoretical description of vibrations on basic elements such as itself испытуемое a product and cables of system of a tension are received.